Makna Keberagaman Budaya bagi Mahasiswa Bimbingan dan Konseling Islam dalam Interaksi Sosial di Universitas Islam Negeri Sultan Syarif Kasim Riau - Ranto Maulana Sianturi; Miftahuddin Miftahuddin; Muhammad fahli Zatrahadi (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
Cultural diversity is an inseparable part of social life in Indonesia, including within higher education environments. Differences in ethnicity, language, customs, and regional backgrounds can influence how students interact and adapt to campus social life. These conditions require students to develop tolerance, openness, and adaptability in order to create harmonious social relationships amid cultural diversity. This study aims to explore the meaning of cultural diversity for Islamic Guidance and Counseling students in social interactions at Universitas Islam Negeri Sultan Syarif Kasim Riau. The novelty of this study lies in its focus on the subjective experiences of Islamic Guidance and Counseling students in interpreting cultural diversity and cross-cultural social interactions within an Islamic university setting, which has rarely been examined specifically. This study employed a qualitative method with a descriptive approach. The research subjects consisted of four students selected through purposive sampling based on different ethnic and regional backgrounds. Data were collected through semi-structured interviews, while data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that students interpret cultural diversity as a blessing, a social identity, and a means to get to know one another and build harmonious social relationships. Students also demonstrated tolerance by respecting differences in language, culture, and background among their peers. In addition, several obstacles in social interaction were identified, particularly differences in language, dialect, and communication styles. However, students continued to maintain harmony through mutual respect, solidarity, and the use of Indonesian as a unifying language. The conclusion of this study indicates that cultural diversity has a positive meaning in shaping tolerance, openness, and harmonious social relationships within the university environment.